THE OPTIMISED CONDITIONS OF INDUCTION OF RECOMBINANT RIP rMJC15310 ACTIVITY ISOLATED FROM Mirabilis jalapa L. LEAVES - Astuti, Puji; ., Sudjadi; ., Sismindari (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Ribosome Inactivating Proteins (RIPs) are compounds isolated from plants with ability to inhibit protein synthesis. The inhibition of protein synthesis is due to inactivation of ribosomal RNA through a site-specific deadenylation mediated by RNA N-glycosidase. Reportedly, RIPs mainly possess wide range of bioactivity including antiviral activity against plant infections. Other activities of RIP were as abortifacien, antivirus and anticancer. This study was aimed to isolate and characterize the optimum conditions for inducing the expression of recombinant RIPs isolated from the leaves of Mirabilis Jalapa L. We have been successfully isolated several RIPs and engineered these proteins to be expressed in E. coli. These recombinant proteins were obtained by screening cDNA library originated from the mRNA of Mirabilis jalapa L leaves, and inserted into pUC19 carrying lacZ gene. The presence of recombinant plasmid was tested by using α-complementation assay. Many RIPs have been isolated from plants and these proteins express enzymatic activity by cutting supercoiled double stranded DNA. One RIP namely rMJC15310 was obtained from this study and the proteins having 8kb in size, cut the supercoiled DNA into linear form at the concentration as low as 5 µg. The ability to cut supercoiled DNA increased on inducing its expression with 0.4% IPTG.Key words: Ribosome Inactivating Proteins (RIP), IPTG, Mirabilis jalapa L., recombinant protein